2010
DOI: 10.1177/0193945910383877
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Measure of Complexity Compression in Registered Nurses

Abstract: Researchers in Minnesota have described and validated the phenomenon of Complexity Compression in qualitative studies of registered nurses. Analysis of themes from this research led to the design of a survey to assess nurses' agreement with variables that contribute to their experience of Complexity Compression. The survey was administered to a random sample of 199 registered nurses in Minnesota. Exploratory factor analysis was used to evaluate the attributes of Complexity Compression and its underlying struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…On the contrary, having to instruct students or new staff adds to the workload of nurses (Krichbaum et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the contrary, having to instruct students or new staff adds to the workload of nurses (Krichbaum et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The findings point to a need to acknowledge this dual and unique role and correct the misunderstanding that having students equals additional 'hands' and thereby decreased workload for staff members. On the contrary, having to instruct students or new staff adds to the workload of nurses (Krichbaum et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Al-Faouri et al (2021) found that level of MNC was the lowest in the private sector compared to public and teaching hospitals. Apart from the fact that private hospitals are the least crowded sector in the Jordanian healthcare sector (Mrayyan et al, 2021), the explanation for this finding might be related to the increased workload on nurses in university hospitals as nurses are required to mentor students in their training (Krichbaum et al, 2011). In addition, the teaching hospitals are recognized for relocating nurses to other units that have reduced staffing levels (Amarneh, 2017), which may lead to more unmet nursing care in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…Another CMO revealed that while staff training was generally helpful in increasing content knowledge and confidence, it also created the adverse effects of increasing complexity compression (CC) among staff. The concept of CC, an understudied topic, first appeared in the nursing literature to capture the nature of nursing workflow that involves assuming multiple roles simultaneously and frequent shifting between tasks due to frequent staff turnover and increasing system complexity within healthcare (Krichbaum et al, 2007(Krichbaum et al, , 2011. Containing CC was a central concern for the clinic leadership in their effort to engage frontline staff in the Behavior Checker implementation efforts, which warrants further studies into CC as a possible mechanism that can influence implementation success.…”
Section: Discussionmentioning
confidence: 99%